Assessment of maternal deaths using three delay model at a tertiary care centre in rural Maharashtra, India: retrospective six years study - Ghumare, Jitendra P.; Padvi, Namrata Vasant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal deaths are the social indicators of the human development and hence their place in MDGs and now in SDGs. Even though India has made a great stride in reducing maternal deaths, the differentials in the states are huge ranging from 46 to 237 maternal deaths per 100000 live births. The three delay model assesses the issues in the emergency obstetric care and upon which the interventions can be based to improve maternal health indicators. Methods: Retrospective record based observational study was carried out at an obstetrics and gynecology department of a tertiary care hospital located at Northern Maharashtra region. The records of deliveries, maternal deaths, age of the mothers, their time of presentation with obstetric complication, level of delay and the reason for delay were extracted for the period of 2011 to 2016. Three delays being, level I - delay in decision to seek care, level II - delay in identifying and reaching medical facility, level III - delay in receipt of adequate and appropriate treatment at facility. Results: Out of 54335 deliveries, there were 128 maternal deaths. 80% women died due to complication in their ANC, 55% being in the third trimester of ANC. Major causes of death were preventable, including Eclampsia (21%), Anaemia (17%), PIH (15%), Sepsis, Other infections and haemorrhage. 27% women had delay of level I, 21% had level III and 15% had a mix of two or three level of delays. The reasons for level I delay being Lack of ANC visits, no ANC registration, level II delay being lack of timely transport facility, level III delay being lack of adequate manpower, training, and lack of efficient intensive care facilities. Conclusions: A good quality emergency obstetric care equals good maternal health. It can be achieved by strengthening the health infrastructure, tackling manpower shortages, having better referral linkages.